Analisa Pengaruh Perubahan dan Pengaturan L/G Terhadap Range, Approach, dan Efektifitas Kinerja Menara Pendingin - Basuki, Diah Wilis Lestaring; Asmoro, Wahyu Panji; Santoso, Eko Budi (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
Cooling towers are critical heat exchange systems designed to lower water temperature by dissipating heat into the atmosphere. They are classified into two primary types: natural draft and mechanical draft. Natural draft cooling towers, also known as hyperbolic towers, utilize the temperature gradient between the heated water and the surrounding air to drive airflow without mechanical assistance. In contrast, mechanical draft towers incorporate large fans to enhance air circulation and improve heat dissipation. The interaction between air and water, facilitated by fill material, optimizes heat transfer efficiency by increasing contact time. Evaluating the impact of operational adjustments on key performance metrics, including thermal range, approach, and overall efficiency, is essential for enhancing cooling tower performance. Additionally, these systems can serve as refrigerant coolers in air conditioning applications. This study investigates the influence of variations in the liquid-to-gas (L/G) ratio on cooling tower efficiency, with a focus on temperature reduction, thermal range, and approach. Experimental findings demonstrate that adjustments in operational parameters significantly affect these performance indicators. Under the tested conditions, the cooling tower achieved an effectiveness of 70.94%, with a thermal range of 19°C and an approach temperature of 7.8°C.